HUBUNGAN PEMENUHAN KEBUTUHAN MIKRONUTRIEN DENGAN STATUS ANEMIA PADA REMAJA PUTRI SMAN 1 TAMBAN KABUPATEN BARITO KUALA - Milasari Milasari (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Humans in life experience a developmental phase, covering infancy to old age. Women 2 years of age enter adolescence faster than men. Adolescence is needed to balance the fulfillment of micronutrient needs. Adolescent girls are prone to experiencing micronutrient deficiencies (Fe, Vitamin C and B12) that will affect growth and development. Micronutrein deficiency caused by wrong diet, environmental influences, association (want to slim). Due to lack of micronutrient intake can cause nutritional health problems that are often encountered is iron anemia. Determination of nutrient requirements for micronutrients in general is based on Recommended Daily Allowances (RDA). The aim of the study is to identify the relationship between meeting the needs of micronutrients and anemia status in young women. The type was analytical survey research method with cross sectional design. The sample size were 62, selected using systematic random sampling. Obtained the results of meeting the needs of the micronutrient category quite well as many as 7 people (33.3%) in respondents aged 16 years at body weight